Recent Trends in Plant Protection and its Role in Sustainable Development in Jordan - Mansour, Akel; Salem, Nida’; Al Banna, Luma; Katbeh-Bader, Ahmad; Bahdousheh, Mary; Al Bess, Mohammad (Jordan Journal of Agricultural Sciences, 2021)
In the past fifty years, the use of chemical pesticides in Jordan has increased significantly, especially after the expansion of the protected agricultural sector, with the aim of eliminating pests, and thus increasing production to the maximum. Despite the efficiency of agricultural pesticides in eliminating agricultural pests, the intensive and unregulated use of these pesticides led to the emergence of many complex problems related to agricultural pests, human health, and environmental pollution, which made it difficult to control them. Therefore, it was necessary to go to other methods and methods to combat the agricultural pests reduce damage to humans, soil, and the environment. Accordingly, the control has turned to modern methods of agricultural pest control management, using integrated pest management, which includes various agricultural operations, agricultural quarantine and biological control, the use of resistant varieties, rationalization of the use of pesticides, and other control methods mentioned in this paper. In Jordan, as a result of multiple studies in the field of control, it was found that integrated pest management is the best solution to the problems of intensive use of pesticides to achieve the principles of sustainable development. Therefore, integrated pest management has become commonly used by farmers. This paper aims to record the development in the field of plant protection in Jordan, from the establishment of the Emirate of Transjordan until the centenary of the Jordanian state.